LEADING CAUSES AND POSSIBLE ENVIRONMENTAL CONTRIBUTORS FOR END STAGE RENAL DISEASE IN ALMADINAH REGION IN SAUDI ARABIA - Inass M. Taha; Amr M. El-Shafie (European Scientific Journal, ESJ, 2014)
To find-out the leading causes and the possible environmental contributors for End Stage Renal Disease (ESRD) in Al-Madinah region, KSA.. 156 patients suffering from ESRD and 160 apparently healthy subjects of comparable age and sex were included. None of the participants was occupationally exposed to lead, cadmium and/or mercury. None affection of the control subjects with renal diseases was confirmed. Patients with undefined leading causes for ESRD (44) and an equal number of the control subjects were subjected to determine their blood levels of lead, cadmium and mercury. The study revealed that the main leading causes of ESRD in Al-Madinah region were hypertension, obstructive uropathy and diabetes mellitus. Environmental pollutants of lead (Pb) and cadmium (Cd) contributed to ESRD in Al-Madinah region particularly in urban areas. Mercury (Hg) was not a pollutant in Al-Madinah region. The study recommended early diagnosis and proper control of hypertension, obstructive uropathy and diabetes mellitus. It also recommended regular environmental monitoring for (Pb) and cadmium (Cd) levels and finds the sources of their elevations and efforts should be raised up to eliminate them.